How meat reduction differs from other personal climate actions: Distinct concerns and cultural barriers among EU consumers. (October 2022) - de Boer, Joop; Aiking, Harry
Highlights: Examines the adoption of meat reduction as one of the personal climate actions. Demonstrates that meat reduction is not yet on par with mainstream actions. Analyses how adopters of meat reduction differ from those who just take other actions. Adopters are motivated by broad environmental, social and public health concerns. Incongruences due to the cultural meaning of meat reduction may hamper adoption. Abstract: Meat reduction might become a new extension of the personal climate actions in the European Union (EU), but this development is not without challenges. Focusing on consumers, this paper investigates 1) how meat reduction is related to other climate actions and 2) how adopters of meat reduction and those who just take other actions differ in concerns about world problems and sociocultural characteristics. The data are from Eurobarometer 95.1 (Spring 2021). The analyses revealed that the adoption of meat reduction was related to the adoption of other climate actions, but that it was not on par with mainstream pro-environmental actions. Participants who incorporated meat reduction in their climate actions were more than the others motivated by broad environmental, social and public health concerns. Those who did not incorporate meat reduction scored lower on these concerns and might have been negatively affected by incongruences between the cultural meaning of meat reduction and their cultural identities in terms of right-wing positions, masculinity or social class. The results showed that meat reduction is part of an adoption process and that the Northwestern countries were somewhat further on in this process than the Southern and Eastern countries.